The Effectiveness of Using Per Rectal Oxytocin Drip and Misoprostol on the Amount of Bleeding in Post Partum Sectio Caesarea - Lisa Rosalina; Hilda; Rosalin Ariefah Putri (Formosa Journal of Science and Technology, 2023)
This study aims to determine the effectiveness of using oxytocin drip and misoprostol rectally on the amount of bleeding in post partum sectio caesarea. The research design used in this study was a quasy experiment with a two group posttest design. The study population was post section caesarea mothers who were given the drug misoprostol plus oxytocin drip and oxytocin alone taken from September to November as many as 242. The sampling technique used was accidental sampling and used the slovin formula so that the sample in this study was 72 respondents. The hypothesis test in this study used a parametric statistical test, namely the Independent T-Test. Based on the research results, it can be concluded that oxytocin drip and per rectal misoprostol are effective against bleeding in post partum sectio caesarea mothers with a p-value of 0.000 (<0.05).